Agricultural transformations in the arid, drought-prone region of Kachchh: People-led, market-oriented growth under adverse climatic conditions - Patel, Praharsh M. (Frontiers in Sustainable Food Systems, 2023)
Water availability, soil suitability, and favorable climate are the primary requirements for stable agricultural production. However, due to erratic rainfall and scarcity of irrigation water, arid regions suffer from volatile conditions for agriculture. For example, Kachchh, the westernmost district of India in Gujarat, has an arid climate, with more than half of the area is either partially inundated by seawater or classified as desert. The remaining landmass experiences low (15 Year Annual Normal = 450 mm) and erratic (45 percent Coefficient of Variation) rainfall rendering agriculture in the region, not a promising occupation. But in recent years, access to irrigation through groundwater, the advent of micro-irrigation practices, and increasing market-oriented crops supported by regular rainfall have led to significant agricultural improvement for the region. As a result, there has been a significant shift toward less water-intensive and high-value horticulture crops. This paper ponders upon drivers of agricultural transformations in Kachchh combining the quantitative observation data and qualitative field insights. It also highlights hurdles to the smooth adoption of drought-resilient and market-oriented agriculture during the adverse climatic conditions.